Cover Feature: Cost‐Effective Vat Orange 3‐Derived Organic Cathodes for Electrochemical Energy Storage (Batteries & Supercaps 2/2023). Issue 2 (18th January 2023) - Chen, Ling; Xing, Fangfang; Lin, Qiting; Waqas, Ahsan; Wang, Xiujuan; Baumgartner, Thomas; He, Xiaoming
Abstract : The Cover Feature illustrates the Vat Orange 3 based energy storage devices. The Monkey King, one of Chinese classic cartoon characters, stepping on the "vat orange 3" cloud, is starting his battle journey. More information can be found in the Research Article by T. Baumgartner, X. He and co‐workers .